Software Requirements: Encapsulation, Quality, and Reuse - Lutowski, Rick (CRC Press, 2009)
Software Requirements: Encapsulation, Quality, and Reuse describes how to make requirements easy to change by using encapsulation. It introduces the Freedom methodology that shows how to encapsulate requirements thereby promoting reuse and quality. Encapsulating requirements reduces software life cycle costs by making requirements and the code that implements them more adaptable to changing technology and business needs.